Exploring life : the principles of biology - Blamire, John. (Dubuque, Iowa : Wm. C. Brown Publishers, 1994)
"This book is intended for use in introductory level courses, in short general biology courses (one quarter or one semester), and possibly in those courses that require an overview of biology before specializing other majors. Biology is the science of life, but for many students, the principles of science are so mysterious and threatening, they never get past their fears and on to the fascinating realm of living creatures that inhabit every good biology course. Between the pages of this book, therefore, the two themes of science and of life are brought together in a way that makes the biology accessible and the science much less intimidating. Any student who is interested in biology but who has little experience with the process of science, will find it possible to learn the principles of biology by following the text. Science is presented as a living process carried out by living scientists in a true context. We see how their work reveals a little more each day about how life works."
Includes index.
Includes bibliographical references.
English text.
Keywords: Biology